Informatics - Nalawade, Mansi; Lalit, Tanmayee (Journal of Engineering Education Transformations, 2010)
*Â National Level Seminar on Quality Enhancement in Higher Education and Research. *Â International Conference on "Higher Education for Knowledge Based Society: Global Reforms".